2006
DOI: 10.2164/jandrol.05076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Outcomes of Cryopreserved Surgically Retrieved Sperm for IVF/ICSI

Abstract: ABSTRACT:We evaluated our experience to date with in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) after either cryopreserved sperm or sperm produced on the date of IVF/ICSI was used. We performed a retrospective statistical analysis of data derived from 188 women undergoing IVF/ICSI cycles using surgically retrieved sperm. A total of 318 IVF/ICSI treatment cycles with 3280 ova were performed using testicular sperm extraction (TESE, 304 cycles) or microsurgical epididymal sperm aspiration (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, fertilization rates and PRs with motile sperm were comparable in the same study, in the fresh testicular tissue or frozen-thawed sperm (77% vs. 70% and 38.8% vs. 33.9%, respectively). Wald et al (34) reported that a PR with cryopreserved testicular sperm did not differ from that achieved with fresh sperm (27.3% vs. 27%) with ICSI. Cayan et al (35) compared the outcome of ICSI with fresh and cryopreserved epididymal spermatozoa from the same couple and reported the clinical PRs as 31.6% with fresh and 36.8% with frozen-thawed spermatozoa.…”
Section: Discussionmentioning
confidence: 96%
“…However, fertilization rates and PRs with motile sperm were comparable in the same study, in the fresh testicular tissue or frozen-thawed sperm (77% vs. 70% and 38.8% vs. 33.9%, respectively). Wald et al (34) reported that a PR with cryopreserved testicular sperm did not differ from that achieved with fresh sperm (27.3% vs. 27%) with ICSI. Cayan et al (35) compared the outcome of ICSI with fresh and cryopreserved epididymal spermatozoa from the same couple and reported the clinical PRs as 31.6% with fresh and 36.8% with frozen-thawed spermatozoa.…”
Section: Discussionmentioning
confidence: 96%
“…According to other studies, in vitro fertilization outcomes using cryopreserved testicular sperm samples are no different from those using fresh specimens (30)(31)(32)(33)(34). However, in cases of nonobstructive azoospermia, uncertainty still exists concerning the possible superiority of one of these sperm-handling methods (35).…”
Section: Fertility Preservation Options In the Adult Malementioning
confidence: 99%
“…A recent review of the data concerning IVF/ICSI outcomes with cryopreserved versus fresh sperm showed overall comparable fertilization rates (39.0-61.7% and 47.0-61.9%, respectively) and clinical pregnancy rates (20-41% and 23-33%, respectively) reported for frozenthawed and fresh sperm [47 ]. High fertilization and pregnancy rates were reported in IVF/ICSI treatments using fresh sperm obtained by TESE, in both obstructive and nonobstructive azoospermia patients [16][17][18].…”
Section: Cryopreserved Versus Fresh Spermmentioning
confidence: 99%
“…While some authors reported lower fertilization and pregnancy rates with frozen-thawed sperm compared with fresh, others demonstrated similar IVF/ICSI outcomes for both sperm-handling methods [3, [48][49][50][51][52]. We recently reported our experience to date with IVF/ICSI after either fresh or cryopreserved sperm was used [47 ]. This large study involved retrospective analysis of data derived from a total of 318 IVF/ICSI treatment cycles with 3280 ova, using TESE (304 cycles) or MESA (14 cycles).…”
Section: Cryopreserved Versus Fresh Spermmentioning
confidence: 99%